Management of Postnatal Depression: A Systematic Review of Clinical Practice Guidelines - Aliya Durrani; Nishani Fonseka; Ram Bajpai; Tom Kingstone; Saeed Farooq (BJPsych Open)
Aims: Postnatal Depression (PND) is the most prevalent mental health disorder during the postpartum period. Evidence suggests that clinical practice guidelines (CPGs) have the potential to improve the mental well-being of these women. A systematic review of the CPGs for PND, addressing both pharmacological and non-pharmacological recommendations, is currently lacking in the literature. We aim to identify the existing CPGs for the management of PND and to collect the specific recommendations reported by them.